Prolapsing right atrial myxoma: clinical and heamodynamic considerations. Issue 5 (May 1977) - Roguin, N; Amikam, S; Riss, E
Abstract : A 22-year-old woman with a right atrial myxoma prolapsing to the right ventricle is described. The haemodynamic findings were similar to those of cases of prolapsing myxoma of the left atrium; a notching on the ascending limb of the right ventricular pressure curve, and an initial negative, irregular deflection on the pulmonary artery pressure curve with a pronounced rise in the mean right atrial pressure (18 mmHg) were found. On deep inspiration there was a significant deepening of the y descent from 12 mmHg to 2 mmHg, indicating a changing, dynamic obstruction of the right ventricle inflow tract. These haemodynamic features can be helpful in the diagnosis of prolapsing right atrial myxoma.